Correction: Working life sequences over the life course among 9269 women and men in Sweden; A prospective cohort study. - Katalin Gémes; Katriina Heikkilä; Kristina Alexanderson; Kristin Farrants; Ellenor Mittendorfer-Rutz; Marianna Virtanen (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0281056.].